2012
DOI: 10.1111/1475-6773.12012
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Use of Gynecologic Oncologists for Women with Ovarian Cancer in the United States

Abstract: Objective. To examine disparities in utilization of gynecologic oncologists (GOs) across race and other sociodemographic factors for women with ovarian cancer. Data Sources. Obtained SEER-Medicare linked dataset for 4,233 non-Hispanic White, non-Hispanic African American, Hispanic of any race, and Non-Hispanic Asian women aged 66 years old diagnosed with ovarian cancer during 2000-2002 from 17 SEER registries. Physician specialty was identified by linking data to the AMA master file using Unique Physician Iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
(75 reference statements)
1
4
0
Order By: Relevance
“…Data from a single state cancer registry study by Chan et al [ 14 ] showed that women with OC under the care of GOs were more likely to receive appropriate staging and chemotherapy treatments, controlling for age, stage, and grade of disease. Also similar to previous studies, our results suggest that greater utilization of GOs in the care of OC patients would be beneficial [ 22 ] . Although the level of detail in our analysis is unable to discriminate the factors underlying the low utilization, it is likely that our results reflect a complex interaction of both preference and access-relevant effects, such as the influence of a patient’s choice in receipt of GO care vs a shortage of available GOs in some areas.…”
Section: Discussionsupporting
confidence: 90%
“…Data from a single state cancer registry study by Chan et al [ 14 ] showed that women with OC under the care of GOs were more likely to receive appropriate staging and chemotherapy treatments, controlling for age, stage, and grade of disease. Also similar to previous studies, our results suggest that greater utilization of GOs in the care of OC patients would be beneficial [ 22 ] . Although the level of detail in our analysis is unable to discriminate the factors underlying the low utilization, it is likely that our results reflect a complex interaction of both preference and access-relevant effects, such as the influence of a patient’s choice in receipt of GO care vs a shortage of available GOs in some areas.…”
Section: Discussionsupporting
confidence: 90%
“…The age group of women 65 years old and older is particularly vulnerable to this cancer: incidence rates are 6 times and mortality rates are 13 times higher in the older population than in women younger than 65 [1]. The advances in treatment have improved the prognosis for ovarian cancer; however, not all women diagnosed with this disease, in particular older women, receive care congruent with current evidence-based guidelines, including the National Comprehensive Cancer Network (NCCN) guidelines [1–4]. …”
Section: Introductionmentioning
confidence: 99%
“…6,8,15,24,26,27 Studies have demonstrated that Black populations have worse survival due to barriers to receipt of quality care, 28,29 including late diagnosis, higher comorbidity burden, 30 and less access to high-volume surgeons. 31,32 HCA is well recognized as a fundamental contributor to receipt of appropriate OC treatment, but most prior studies only evaluated one dimension or component of HCA, 31,[33][34][35] whereas this study attempts to comprehensively capture multiple dimensions of HCA. We found that patients with higher affordability were more likely to receive guideline-concordant surgery and initiate and complete chemotherapy, which is consistent with past findings that low SES is associated with lower likelihood to undergo surgery or receive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%